Analisis Potensi Pemanfaatan Kualitas Air Hujan Untuk Penggunaan Non-potable Water di Kampus Universitas Andalas - Ermaningsih; Nur, Ansiha; Komala, Puti Sri (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The high demand water for sanitation purposes in Engineering Faculty, Andalas University, particularly for toilet flushing systems, has not been balanced by utilization of sustainable alternative water sources. Therefore, this study aims to evaluate feasibility of rainwater quality as non-potable water source planned for implementation in the buildings of Engineering Faculty, Andalas University. The feasibility assessment refers to Regulation of Health Minister of Republic of Indonesia Number 2 of 2023. Rainwater samples collected directly from building roof downpipes, with three repetitions at the same location. The parameters of pH, dissolved oxygen (DO), and temperature were measured in situ using Lutron DO-5510 dissolved oxygen meter and portable pH meter, while turbidity, BOD, COD, TSS, and total coliform were analyzed at Environmental Engineering Department Laboratory of Andalas University using standard methods based on SNI 6989.57:2008 and US EPA Method 1699. The results indicate that pH, DO, temperature, BOD, COD, TSS, and turbidity comply with the established quality standards, whereas total coliform levels exceed the permissible limit. The presence of total coliform is presumably due to contamination from bird droppings on roof surfaces, particularly in areas surrounded by vegetation.